A clean energy Korea by 2035: Transitioning to 80% carbon-free electricity generation - Won Young Park; Yong Hyun Song; Nikit Abhyankar; Hee Seung Moon; Umed Paliwal; Eunsung Kim; Nina Khanna; Sanghyun Hong; James Hyungkwan Kim; Kenji Shiraishi; Jiang Lin; Seung Wan Kim; et al. (Cell Reports Sustainability)
Summary: South Korea relies on imported fossil fuels for over 60% of its electricity generation, making it vulnerable to energy security risks and fuel price volatility. This study analyzes pathways for South Korea to achieve an economically optimal clean electricity generation mix by 2035, using capacity expansion and production cost modeling. We find that transitioning to 80% clean electricity—comprising 50% renewables and 30% nuclear—alongside investments in storage and transmission is both economically desirable and operationally feasible. Expanding renewables can reduce dependence on imported natural gas and coal while dramatically reducing emissions. Declined clean energy costs can reduce electricity supply costs by 23%–40% compared with 2022. Hourly dispatch simulations indicate that South Korea’s grid can integrate high levels of variable renewables without coal generation or new natural gas power plants. Realizing these benefits requires ambitious policies, a robust regulatory framework, and effective business models to spur renewable energy growth. Science for society: South Korea’s heavy dependence on fossil fuels presents a significant challenge, requiring urgent and sustained action to ensure a sustainable and resilient energy future. We analyze economic decarbonization pathways for Korea’s electric power sector by 2035, leveraging optimal capacity expansion and hourly dispatch modeling to assess the opportunities and constraints in the power systems and reflecting expected rapid declines in the costs of solar, wind, and battery storage technologies. We also introduce offshore high-voltage direct current transmission lines as a strategic network planning option to address the significant discrepancies between major load centers and high-potential renewable energy regions. We find that accelerated renewable energy deployment by 2035 is achievable in a cost-effective and reliable manner, offering substantial economic, environmental, and energy security benefits. We thus present a comprehensive perspective on Korea’s energy transition in the power sector.